(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
Present paper dedicated to moss biomonitoring technique issues as a multi-media tool of pollution control. In recent years, this method has become a popular way of controlling the level of environmental pollution. In many studies, method of biomonitoring with mosses has proven to be relatively accurate, practical and simple method. Nevertheless, a number of shortcomings and questions have been identified through series of studies. One of the most important questions is what kind of moss biomonitoring method we should use – passive or active biomonitoring? Despite the large number of publications and the continued use of the transplant method, there are also a number of serious unresolved issues. In particular, there is no consensus on the optimal exposure duration, moss type, moss bag form, quantity of samples and pre-experimental preparations. All the problems that were listed below a considerable barrier on the way of standardization of this technique. This review paper collected and analyzed moss biomonitoring studies in order to present different experimental methods and experimental preparations of biomonitoring control of air and water pollution used in different study, and to present advantages and disadvantages of this technique and show the future perspective and possible solutions